2021
DOI: 10.3389/fvets.2021.672716
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Antimicrobial Resistance Phenotypes, and Virulence Genes of Bordetella bronchiseptica From Pigs in China, 2018–2020

Abstract: Bordetella bronchiseptica is a leading cause of respiratory diseases in pigs. However, epidemiological data of B. bronchiseptica in pigs particularly in China, the largest pig rearing country in the world is still limited. We isolated 181 B. bronchiseptica strains from 4259 lung samples of dead pigs with respiratory diseases in 14 provinces in China from 2018 to 2020. The average isolation rate of this 3-year period was 4.25% (181/4259). Antimicrobial susceptibility testing performed by disc diffusion method r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…In this experiment, Bb had the highest resistance to lincomycin, with a resistance rate of 100%, and was relatively sensitive to ciprofloxacin, with a resistance rate of 17.86%. Another report [ 23 ] showed that Bb had the highest resistance to ampicillin, with a resistance rate of 83.98%, and there were 6 antibiotics with associated resistance rates of 0% in China. E. coli was had the highest resistance to tilmicosin and lincomycin, with resistance rates of 100%, and the highest sensitivity to cefotaxime, with a resistance rate of 15.96%.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, Bb had the highest resistance to lincomycin, with a resistance rate of 100%, and was relatively sensitive to ciprofloxacin, with a resistance rate of 17.86%. Another report [ 23 ] showed that Bb had the highest resistance to ampicillin, with a resistance rate of 83.98%, and there were 6 antibiotics with associated resistance rates of 0% in China. E. coli was had the highest resistance to tilmicosin and lincomycin, with resistance rates of 100%, and the highest sensitivity to cefotaxime, with a resistance rate of 15.96%.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors such as Knezevic et al [ 34 ], suggested that MOI 10 is the most appropriate for a successful antibacterial phages effect because at this MOI each bacterium is infected by at least one phage following the Poisson distribution. However, when temperate phages are examined, the effect of different MOIs on phage lytic activity is different [ 15 , 50 ]. One example is the lambda phage, for which phage integrase activity directly depends on the concentration of cell proteases and MOI value: a low concentration of protease or high MOI values enhance integrase activity, which promotes phage entry into the lysogenic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine for B. bronchiseptica , commonly used since 1970s, is unreliable as it does not provide long-term immunity [ 11 , 12 ]. In addition, the increased degree of resistance to B. bronchiseptica isolates against commonly used antibiotics, including β-lactams, macrolides and tetracyclines, has become a serious concern [ 13 , 14 , 15 ]. In the last few years, the use of bacteriophages in the treatment of bacterial infections has gained the attention of the scientific community [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%